Comprehensive multicomponent cardiac rehabilitation in cardiac implantable electronic devices recipients: a consensus document from the European Association of Preventive Cardiology (EAPC; Secondary prevention and rehabilitation section) and European Heart Rhythm Association (EHRA). (26th January 2021) - Pedretti, Roberto F E; Iliou, Marie-Christine; Israel, Carsten W; Abreu, Ana; Miljoen, Hielko; Corrà, Ugo; Stellbrink, Christoph; Gevaert, Andreas B; Theuns, Dominic A; Piepoli, Massimo F; Reibis, Rona; Schmid, Jean Paul; et al.
Abstract: Cardiac rehabilitation (CR) is a multidisciplinary intervention including patient assessment and medical actions to promote stabilization, management of cardiovascular risk factors, vocational support, psychosocial management, physical activity counselling, and prescription of exercise training. Millions of people with cardiac implantable electronic devices live in Europe and their numbers are progressively increasing, therefore, large subsets of patients admitted in CR facilities have a cardiac implantable electronic device. Patients who are cardiac implantable electronic devices recipients are considered eligible for a CR programme. This is not only related to the underlying heart disease but also to specific issues, such as psychological adaptation to living with an implanted device and, in implantable cardioverter-defibrillator patients, the risk of arrhythmia, syncope, and sudden cardiac death. Therefore, these patients should receive special attention, as their needs may differ from other patients participating in CR. As evidence from studies of CR in patients with cardiac implantable electronic devices is sparse, detailed clinical practice guidelines are lacking. Here, we aim to provide practical recommendations for CR in cardiac implantable electronic devices recipients in order to increase CR implementation, efficacy, and safety in this subset of patients.